Mission in Simplicity of Heart and Mind: Ludwig Harms and the Founding of the Hermannsburg Mission - Grundmann, Christoffer H. (Missiology, 2012)
The formation of the Hermannsburg Mission in 1849 by Pastor Ludwig Harms (1808–1865) represents the beginning of a vibrant mission initiative that became one of the largest within German Protestantism. It also set the stage for a particular perception of missionary service and practice, a perception still worth serious consideration today. The article, first of all, familiarizes the reader with the person of Ludwig Harms, then it presents his missionary principles, and finally, it offers a critical evaluation of his legacy that can be summarized as follows: If you want to win the world for Christ, start living a Christian life at home.